The Scenography of Josef Svoboda (Wesleyan University Press, 1974)
One of the Czech Republic's most innovative scene designers, incorporating multimedia aspects into his scene designs, Josef Svoboda's (1920-2002) work is made available to the Anglophone public with translations from Jarka Burian (1927-2005). A detailed study of sixty key productions designed by Svoboda with over two hundred black-and-white photographs, Svoboda's scenography is realized as a synthesis of traditional methods with technical innovations, creating a total design experience.